2011
DOI: 10.1021/jp111335w
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Dissociative and Molecular Water Adsorption on Anatase TiO2(101)

Abstract: The adsorption properties of water on the stoichiometric (101) surface of anatase TiO2 in the temperature range 160–400 K has been studied by synchrotron radiation core level photoelectron spectroscopy. O 1s spectra give clear evidence for the formation of a first layer of water that comprises both H2O and OH. The composition is 0.77 ± 0.05 ML H2O and 0.47 ± 0.05 ML OH. Decreasing the coverage by heating leads to a decreased H2O/OH ratio. The results are very similar to those recently reported for water on rut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
160
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(193 citation statements)
references
References 36 publications
32
160
0
1
Order By: Relevance
“…[87]. Chemically dissociated water molecules were shown to be energetically favored on {001} facets, whereas water molecules are expected to physically adsorb on {101} surfaces [13,18,88], though partial dissociation within the first layer of water on anatase surface was recently observed by Walle et al by surface-sensitive photoelectron spectroscopy [89]. Anyway, by considering that dissociated water may facilitate the transfer of photogenerated carriers and the formation of reactive radicals, {001} facets are expected to be much more effective for photo-redox reactions than {101} facets.…”
Section: Dissociative Adsorptionmentioning
confidence: 97%
“…[87]. Chemically dissociated water molecules were shown to be energetically favored on {001} facets, whereas water molecules are expected to physically adsorb on {101} surfaces [13,18,88], though partial dissociation within the first layer of water on anatase surface was recently observed by Walle et al by surface-sensitive photoelectron spectroscopy [89]. Anyway, by considering that dissociated water may facilitate the transfer of photogenerated carriers and the formation of reactive radicals, {001} facets are expected to be much more effective for photo-redox reactions than {101} facets.…”
Section: Dissociative Adsorptionmentioning
confidence: 97%
“…The interpretation of STM images for higher * feliciano.giustino@materials.ox.ac.uk coverages proved more challenging due to the appearance of an unexpected 2×2 superstructure. Then, in contrast with the prevailing view of molecular adsorption of water on anatase, the authors of a recent high-resolution XPS study [21] reported the presence of OH groups at the surface, and challenged the accepted model of the interface. From an analysis of the XPS spectral intensities the authors of Ref.…”
Section: Introductionmentioning
confidence: 95%
“…From an analysis of the XPS spectral intensities the authors of Ref. [21] proposed that, at monolayer coverage, 23±5% of the water molecules dissociate into a hydroxyl and a proton.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations